CONSORT: Effects of adding adefovirdipivoxil to peginterferon alfa-2a at different time points on HBeAg-positivepatients. Issue 31 (August 2016) - Zhang, Ka; Cao, Hong; Liang, Jiayi; Shu, Xin; Sun, Haixia; Li, Gang; Xu, Qihuan
Abstract: Background: The aims of this study were to compare the efficacy and safety of the addition of adefovir dipivoxil (ADV) (started at different time points) to pegylated interferon alpha-2a (PEG-INF-α2a) and PEG-INF-α2a monotherapy. This prospective, randomized study sought to evaluate the safety and efficacy of the combination of PEG-INF-α2a and ADV at different time points.120 patients were randomized into groups that received PEG-INF-α2a as monotherapy (group A) or in combination with ADV started at week 0 (group B), 12 (group C), or 24 (group D). All patients were followed for 48 weeks. Efficacy and safety analyses were performed. Methods: Patients in group a received 135 μg of PEG-INF-α2a by subcutaneous injection once weekly for 48 weeks. Patients in the ADV add-on group received 135 μg of PEG-INF-α2a subcutaneously once weekly and received 10 mg of ADV administered once daily for 48 weeks. HBV DNA, HBsAg, HBeAg, and hepatitis B e antibody levels were determined. Responses were determined at week 12 (ADV add-on), the end of treatment for PEG-INF-α2a (48weeks) and ADV (EOT) and at the end of 96 weeks of follow-up (EOF). Results: The rate of HBV DNA loss were higher in the combination groups than group A at the week 12, week 48, the EOT and EOF (P < 0.05). The rates of HBeAg seroconversion and HBsAg loss were similar among the treatment groups (P>0.05). The alanineaminotransferase (ALT) normalization rate was higher in the combination group than group A only at the EOT (P = 0.007). By the EOF, the patients with ADV added at week 12 achieved higher rates of HBV DNA loss (71.9%), HBeAg seroconversion (50.0%), HBsAg loss (15.6%), and ALT normalization (78.1%). Conclusions: PEG-INF-α2a plus ADV combination therapy is safe and superior to PEG-INF-α2amonotherapyfor decreasing serum HBV DNA and normalizing the ALT level but has no significant impact on the rate of HBeAg seroconversion and HBsAg loss. Adding ADV at week 12 may be an optimal combination strategy.